2014
DOI: 10.1038/ncomms5433
|View full text |Cite
|
Sign up to set email alerts
|

Economic photoprotection in photosystem II that retains a complete light-harvesting system with slow energy traps

Abstract: The light-harvesting antenna of higher plant photosystem II has an intrinsic capability for self-defence against intense sunlight. The thermal dissipation of excess energy can be measured as the non-photochemical quenching of chlorophyll fluorescence. It has recently been proposed that the transition between the light-harvesting and self-defensive modes is associated with a reorganization of light-harvesting complexes. Here we show that despite structural changes, the photosystem II cross-section does not decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 34 publications
3
61
0
Order By: Relevance
“…The PSII as the heart of the photosynthetic process is highly sensitive to the environmental stresses. Its activity could be determined with one non-invasive time-resolved fluorescence measurement, which could measure the polyphasic rise with the basic steps of OJIP [43,[48][49][50][51][52][53][54]. Several studies have shown that the chlorophyll a transient has become one of the most popular tools to estimate stress-induced changes in photosynthetic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The PSII as the heart of the photosynthetic process is highly sensitive to the environmental stresses. Its activity could be determined with one non-invasive time-resolved fluorescence measurement, which could measure the polyphasic rise with the basic steps of OJIP [43,[48][49][50][51][52][53][54]. Several studies have shown that the chlorophyll a transient has become one of the most popular tools to estimate stress-induced changes in photosynthetic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no denial that the LHCII antenna undergoes reorganization into the NPQ state, recent data suggest that it does not uncouple energetically from RCII (Johnson and Ruban, 2009;Belgio et al, 2014), as was previously proposed (Holzwarth et al, 2009), which is in total agreement with the earlier established and experimentally confirmed relationship between the yield of PSII and NPQ (Genty et al, 1989). Moreover, it was shown that NPQ protects closed, not open, RCII, which makes this protective strategy economical, as it does not allow much competition between NPQ and RCII traps for energy under low or moderate light intensity .…”
Section: Change: Lhcii Rearrangements/aggregation and The Formation Omentioning
confidence: 99%
“…Whole leaves were removed from plants after 45 min dark adaptation and then subjected to three saturating pulses (1000 lmol m -2 s -1 , 0.6 s width). Vacuum infiltration was then performed on leaves with 10 mM Hepes pH 7.5, 150 mM sorbitol and 30 lM DCMU (for more details, see Belgio et al 2012Belgio et al , 2014. 20 s after infiltration, a pre-programmed fast trigrun (Walz, Germany) of 7 lmol m -2 s -1 measuring light intensity was performed.…”
Section: Psii Fast Fluorescence Induction Measurementsmentioning
confidence: 99%
“…These values were taken from a number of previous reports (Pessarakli 2005;Dall'Osto et al 2006;Caffarri et al 2009;Amunts et al 2010). For more details see Table 1 from Belgio et al (2014). Chlorophyll a/b ratios of each photosystem component were taken from Table 2 in Hogewoning et al (2012).…”
Section: Absorption Spectroscopymentioning
confidence: 99%